(3QSGdI aj Yde GdMSGHs - (3GdbGgQj, GdRjGJ, GdTGaYj, GdSNGhj, GHf TYHGf, Rjf GdOjf, YHO GdbGOQ Hf Ydj Hf TYHGf (B, (3J (B892 (3g`s
(3ChdgG (B:s
(3GdMeO ddg gPG eNJUQ aj Yde GdMSGH Sgd ddeHJOF fGaY Ef TGA Gddg JYGdi QJHJg Ydi ebOeI hEMOi YTQ HGHG hNGJeI aGdebOeI aj UaI GdCMQa GdgfOjI hgj CTcGdgG s
(3BNQgG (B:s
(3aUd aj GdeMGUI hgj eOjGf Ydjg dRjO YTQI hdYeQh YTQhf hdHcQ KdGKhf ahLO dg NeSI hYTQhf aGLeY GdOjhf jcf eLehYgG SJhf GJNPgG EeGeG hfSHI cd MUI Edjg Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\191s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdQjGVjGJs